Developed black beaches - too hot to emerge? Factors affecting sand temperatures at nesting grounds of olive ridley sea turtles (Lepidochelys olivacea) - Daniel Ariano-Sánchez; Anita Nesthus; Frank Rosell; Stefanie Reinhardt (Climate Change Ecology, 2023)
Climate change research on sea turtles has focused on the impact of rising temperatures on sex ratios, while the thermal ecology of natural nesting grounds has received less attention. Many nesting beaches are highly affected by vegetation loss and urbanization which in turn may affect their thermal profile, particularly at beaches with dark volcanic sand. We studied the sand temperatures on two urban-developed volcanic sea turtle nesting beaches in Guatemala for two years, and their potential effect on the thermal ecology of sea turtle nests by using the olive ridley as model species. We hypothesized that local weather, type of cover at surface, and season (dry vs rainy) will have a pronounced effect on sand temperatures, potentially affecting the hatching success of sea turtles. Average sand temperatures at nesting beaches were almost always above the pivotal temperature (87% of days), and either close to or above the thermal maximum tolerance of sea turtle embryos over longer periods (78% of days). We found that higher air temperatures led to higher sand temperatures, and high relative humidity and precipitation led to lower sand temperatures. As expected, sand temperatures in plots covered by vegetation were lower (32.5 ± 2.8°C) than those without vegetation cover (33.1 ± 2.6°C). Plots close to concrete structures showed the highest sand temperatures (34.0 ± 3.2°C). Our results highlight the relevance of vegetation in buffering the effects of high sand temperatures, which will have profound implications for the resilience of olive ridleys to global warming.